MICROWAVE SYNTHESIS OF B-TIPE CARBONATED HYDROXYAPATITE: UDC 546.41-31-325 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Phase formation of carbonated hydroxyapatite in microwave synthesis conditions was investigated. The possibility of phosphateanions selective substitution by carbonate group was shown in that conditions. Obtained compounds were investigated withXRD-analysis and IR-spectroscopy
Keywords: -